Generation X, Y and Z: Impact of internal communication on employee satisfaction and commitment - Mihajlo Đurović; Sandra Dramićanin; Dragana Milenković (BizInfo)
This study aimed to analyze the effect of internal communication on employee job satisfaction and commitment depending on the generation to which an employee belongs. Nowadays, when organizations function with multigenerational employees, all employees must communicate and cooperate in a certain way, to achieve set goals and overall benefits. There is no universal path to success or a way for multigenerational human resources to function perfectly, but preferences in the way of internal communication that satisfies a certain generation and their mutual alignment can help overcome common challenges that occur in the work environment, and employees are dedicated to the daily performance of their activities. Organizations with dedicated employees have higher revenues and productivity; therefore, it is necessary to consider the importance of internal communication for employee commitment. The results show that internal communication has a positive effect on employee job satisfaction and commitment. The most significant positive correlation between internal communication and employee job satisfaction was observed in Generation Z, whereas the most significant positive correlation between internal communication and employee commitment was observed in Generation X. The results of this study can serve to fill the gap in research on the impact of internal communication on satisfaction and commitment according to the generation to which employees belong.